Comparison of Mean Bowel Cleanliness Score in Patients Undergoing Colonoscopy Prepared by Sodium Phosphate versus Polyethylene - Sonia Saleem, Muhammad Azhar Waseem, Saad Hassan Khan, Muhammad Yasir Younis, Sadia Jabbar, Asmat Ullah (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Adequate bowel preparation is essential for accurate colonoscopy. Both oral sodium phosphate (NaP) and polyethylene glycol-based lavage (PEG-ELS) are used predominantly as bowel cleansing modalities. However, NaP has gained popularity due to low drinking volume and lower costs. Objective: To compare the mean bowel cleanliness score in patients undergoing colonoscopy prepared by sodium phosphate vs. polyethylene glycol. Study Design: It’s a randomized controlled trial Settings and Duration: Department of Gastroenterology Shaikh Zayed Hospital, Lahore, 6 months after the approval of synopsis, from Nov 2019 to April 2020. Methodology: After approval from ethical review committee of the hospital, 100 cases (50 in each group) patients who presented in Department of Gastroenterology Shaikh Zayed Hospital, Lahore and who fulfilled the criteria were counselled and explained the details of the study. Written informed consent and detailed history was taken from each patient. These patients were then randomly divided into following two groups using lottery method, Group-S: Sodium phosphate and Group-P: polyethyelene glycol. Cleanliness of the colon was noted as per operational definition. All the data was noted and recorded into the attached proforma along with demographic details of the patient. All the colonoscopies were done by the endoscopists with a same single observer recording the findings to eliminate bias, and confounding variables were controlled by exclusion. Results: In our study, of 100 cases (50 in each group) 48%(n=24) in Group-S and 52%(n=26) in Group-P were between 18-50 years of age whereas 52%(n=26) in Group-S and 48%(n=24) in Group-P were between 51-70 years of age, mean+sd was calculated as 51.64+8.82 years in S and 51.24+8.67 in P groups, 50%(n=25) in Group-S and 60%(n=30) in Group-P were male whereas 50%(n=25) in Group-S and 40%(n=20) in Group-P were females. Comparison of mean bowel cleanliness score in patients undergoing colonoscopy prepared by sodium phosphate vs. polyethylene glycol shows that Group-S had 3.82+0.92 and Group-P had 2.68+0.68 cleanliness score, p value was 0.0001. The results of our study are comparable with the above study. Conclusion: We concluded that the mean bowel cleanliness score was significantly better in patients undergoing colonoscopy prepared with sodium phosphate when compared with polyethylene glycol.